PENGARUH PELATIHAN DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN - FIRDIYANTI, ERWIN (Jurnal Ilmu Manajemen (JIM), 2017)
This study aims to examine the partial and simultaneous influence between training and motivation on work productivity on department production PT. Subaindo Cahaya Polintraco. Data obtained from the result of questionnaires and interviews. The Analytical techniques used are descriptive statistics and inferential statistics with application from PLS (Partial least square) as data management. The sample used a saturation sample, which is 40 employees.The results in this study indicate that the training has not significant effect on work productivity, because The training provided is often done and understood by employees who majority have worked for more than 5 years, so their skills are good. Motivation has a positive and significant effect on work productivity . Training and motivation have simultaneous influence on work productivity. Keywords: Training, Motivation, Employee Productivity